EDUKASI DAN PENDAMPINGAN LABEL PANGAN, BRANDING, DAN AKUNTANSI SEDERHANA SEBAGAI UPAYA PENINGKATAN DAYA SAING PRODUK UMKM DI KAWASAN PARIWISATA NASIONAL CANDI BOROBUDUR DESA WRINGINPUTIH, KAB. MAGELANG - Afif, Naufal; Suryatimur, Kartika Pradana; Iskandar, Nabila Faradina; Utami, Martiana Riawati (Jurnal Abdi Insani, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play an important role in supporting the regional economy, especially in tourist areas. However, many MSMEs still face obstacles such as simple packaging without labels, lack of halal certification, and weak financial management. These conditions reduce the competitiveness of MSMEs in accessing modern markets and exports. This community service activity was carried out to improve MSME actors' understanding and skills in food labeling, branding, and financial management. The purpose of this activity was to provide education and assistance to MSME actors so that they could improve the legality of their businesses, strengthen product identity, and expand market reach. The activity was carried out through educational outreach, training, and mentoring using a Participatory Rural Appraisal approach. This activity involved partner MSMEs, BUMDes Guyub Rukun, and LP3H halal supervisors. The results of the activity showed that participants understood the importance of food labeling according to standards, acquired the skills to create labels with complete information, and began the process of applying for NIB, PIRT, and halal certification. Participants also gained knowledge about product branding to increase sales value and market differentiation. In addition, they began to implement simple financial record-keeping and learned about digital applications for financial management. This assistance encouraged the creation of MSME products that are better prepared to compete in the modern market and have the potential to enter e-commerce and export markets. In conclusion, this activity improved the capacity of MSMEs in Wringinputih Village in labeling, branding, and finance as a strategy to strengthen business competitiveness